Enhancing and expanding WSTLUR’s leadership and agenda: The urgent need for integrated interdisciplinary research, policy and practice - Giles-Corti, Billie (Journal of Transport and Land Use, 2018)
By 2050, it is estimated that around 6.3 billion people will live in cities (United Nations Population Fund, 2011). Indeed, nearly 70% of humanity will live in cities, representing a unique moment in time in human history. As we hurtle towards this uncertain future, land use, transport, and infrastructure decision-making has never been more important: in the next two decades—and on our watch—the decisions made by the students and professionals taught, advised, and mentored by academics across multiple disciplines—including land use and transport academics—will profoundly impact the sustainability of cities and the health and wellbeing of their residents.